Roles of MIR155HG and TNF-α in Evaluation of Prognosis of Patients with Systemic Lupus Erythematosus: Associations of MIR155HG and TNF-α with Systemic Lupus Erythematosus - Gu, Xiaojing; Chen, Hu; Li, Rongping; Guo, Dibin (Journal of Medical Biochemistry, 2023)
Background: To study the roles of micro ribonucleic acid (miR)-155 host gene (MIR155HG) and tumor necrosis factor-α (TNF-α) in the evaluation of prognosis of patients with systemic lupus erythematosus (SLE). Methods: A total of 130 patients with SLE admitted to our hospital were selected, and the SLE disease activity index (SLEDAI) score was given. The expressions of MIR155HG and TNF-α were detected via quantitative reverse transcription-polymerase chain reaction (qRT-PCR), the incidence of complications during treatment was observed, and the associations of MIR155HG and TNF-α with SLEDAI before treatment and complications were analyzed. All patients were followed up after discharge, and the related factors to the prognosis of patients were analyzed via Cox regression analysis. Results: The levels of MIR155HG and TNF-α were higher in patients with an SLEDAI score of 10-14 points than those in patients with an SLEDAI score of 5-9 points and 0-4 points. MIR155HG and TNF-α were positively correlated with the incidence of infection, renal damage and cardiac damage. Moreover, there was also a positive correlation between the expressions of serum MIR155HG and TNF-α in SLE patients. SLEDAI score ≥10 points, complications during hospitalization, and highly-expressed MIR155HG and TNF-α were risk factors related to the prognosis of patients. Conclusion: MIR155HG and TNF-α are key regulators in the pathogenesis of SLE, and they can affect the prognosis of patients. Such a finding provides potential new targets for the treatment of SLE.